Answer:
First odd number = 13
Second odd number = 15
Step-by-step explanation:
Let
First odd number = 2x + 1
Second odd number = 2x + 3
According to given conditions:
32 + 2x + 1= 3 (2x + 3)
33 + 2x = 6x + 9
Taking terms with x to left and constants to right
2x - 6x = 9 - 33 (sign of transferred terms will be changed)
-4x = -24
Dividing both sides by -4
x = -24/-4
x =6
So,
First odd number = 2x + 1 = 2*6 + 1 = 12 + 1 =13
Second odd number = 2x + 3= 2*6 +3= 12 + 3 = 15
I hope it will help you!
Answer:
Step-by-step explanation:
difference of a number and 9 means to subtract
twice that means multiply by 2
at least is greater than or equal to
It would take them a half and hour